Calidad del servicio en centros residenciales desde la perspectiva de los usuarios/as. Contexto de la Región de Murcia. - LÓPEZ, INMACULADA BAÑOS; SELLER, ENRIQUE PASTOR; VARGAS, CLARA STELLA JULIAO (Cultura de los Cuidados, 2026)
Objective: To establish the quality of service through the perception of the residents of gerontological centers in the region of Murcia, based on the Servperf model. Methodology: mixed study (quantitative and qualitative) with descriptive and correlational scope in which a non-experimental design is followed. The selection of the three residential centers was randomly made using the Excel computer tool. The selection of the participants is carried out with the establishment of inclusion criteria. The sample consisted of 68 residents of both sexes aged between 40 and 96 years. There is no sampling error. A semi- structured questionnaire based on the Servperf model was administered to each participant by means of a personal interview. Results: there are 87 residential centers in the region of Murcia. Residents are more satisfied with the visiting hours of family members and less satisfied with the availability of a variety of food and drink. There is no dimension rated with a score lower than 4. Most residents prefer to be at home. Conclusion: Male and female users are satisfied with the service, although they would prefer to be at home. There is gender differentiation in the degree of satisfaction in the dimensions of reliability and safety. It is a challenge and a commitment to continue improving the quality of the residential service, since it is in this space where thousands of people spend long periods of time until the end of their lives. In this area, the care and good treatment provided by the social and health care professionals are essential to obtain a high degree of satisfaction among residents.